Moss cell walls: structure and biosynthesis - Roberts, Alison W.; Roberts, Eric M.; Haigler, Candace H. (Frontiers in Plant Science, 2012)
The genome sequence of the moss Physcomitrella patens has stimulated new research examining the cell wall polysaccharides of mosses and the glycosyltransferases that synthesize them as a means to understand fundamental processes of cell wall biosynthesis and plant cell wall evolution. The cell walls of mosses and vascular plants are composed of the same classes of polysaccharides, but with differences in side chain composition and structure. Similarly, the genomes of P. patens and angiosperms encode the same families of cell wall glycosyltransferases, yet, in many cases these families have diversified independently in each lineage. Our understanding of land plant evolution could be enhanced by more complete knowledge of the relationships among glycosyltransferase functional diversification, cell wall structural and biochemical specialization, and the roles of cell walls in plant adaptation. As a foundation for these studies, we review the features of P. patens as an experimental system, analyses of cell wall composition in various moss species, recent studies that elucidate the structure and biosynthesis of cell wall polysaccharides in P. patens, and phylogenetic analysis of P. patens genes potentially involved in cell wall biosynthesis.